2019
DOI: 10.15832/ankutbd.539018
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Staphylococcus hominis from Cultured Gilthead Sea Bream (Sparus aurata L.) in Antalya Bay, Turkey

Abstract: In this study, a disease case caused with 15% mortality on gilthead sea bream (Sparus aurata) which was cultured in the Antalya Bay in the Mediterranean coast of Turkey was investigated in July 2015. Lethargy, loss of equilibrium, petechae on the operculums and the dorsal part of the body, pillar of the gills were recorded in the diseased fish. Internally, ascites, splenomegaly and hemorrhages on the intestinal tissue and muscle were observed. Occurrence of parasite was not detected. According to the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…Similar histopathological changes previously reported in staphylococcal infections of fishes (Gaafar et al, 2015;Huang et al, 1999;Timur & Akayli, 2003;Yılmaz et al, 2019) were also observed in the naturally infected fish samples. However, granulomas reported by Huang et al (1999) A two-step pathogenicity assay was designed to confirm the mortalities observed in the field samples and to determine the development stages of staphylococcal infections in the fish tissues.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar histopathological changes previously reported in staphylococcal infections of fishes (Gaafar et al, 2015;Huang et al, 1999;Timur & Akayli, 2003;Yılmaz et al, 2019) were also observed in the naturally infected fish samples. However, granulomas reported by Huang et al (1999) A two-step pathogenicity assay was designed to confirm the mortalities observed in the field samples and to determine the development stages of staphylococcal infections in the fish tissues.…”
Section: Discussionsupporting
confidence: 86%
“…Similar histopathological changes previously reported in staphylococcal infections of fishes (Gaafar et al., 2015; Huang et al., 1999; Timur & Akayli, 2003; Yılmaz et al., 2019) were also observed in the naturally infected fish samples. However, granulomas reported by Huang et al.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Numerous Staphylococcus spp. including S. warneri , S. hominis , S. aureus , S. xylosus , and S. epidermidis have been reported to cause septicemic like symptoms in various fish species (Metin et al, 2014; Oh et al, 2019; Yilmaz et al, 2019). Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Still, S. hominis could be identi ed one among the Staphylococci species from Turkish aquaculture systems by showing signi cant clinical and histopathological changes in shes (Canak and Timur 2020). It was also found to be responsible for hyperplasia and hemorrhages in liver and kidney of cultured gilthead sea bream (Yilmaz et al 2019). Moreover, S. hominis could also found to cause cellulitis and bacteremia in humans and hence raise public concern while managing sh health (Uddin et al 2022).…”
Section: Identi Cation Of Bacterial Isolates From Infected Oscar Shmentioning
confidence: 99%